Flagellar location determines the stability of bacterial surface entrapment - Antai Tao; Sanyuan Fu; Rongjing Zhang; Junhua Yuan (Proceedings of the National Academy of Sciences, 2025)
Surface interactions play a crucial role in shaping the motility patterns and ecological adaptations of swimming bacteria. Previous studies have primarily focused on peritrichous bacteria like Escherichia coli , whose multiple flagella form a bundle during swimming, allowing them to remain trapped at surfaces for extended periods. However, this surface entrapment phenomenon varies significantly among different bacterial species, despite all fitting into the simplified theoretical models of pusher-type bacteria, suggesting that key factors remain unidentified. Here, we demonstrate that flagellar location is a critical determinant of surface entrapment stability in pusher-type bacteria. Using fluorescently labeled Pseudomonas aeruginosa , we show that cells with a single lateral flagellum exhibit substantially longer surface residence times compared to those with a single polar flagellum, despite similar cell morphology and swimming speeds. Through direct visualization of bacterial orientation angles relative to surfaces, we reveal that this difference results from the distinct bending directions of the flagellar hook—the flexible joint connecting the rigid filament to the cell body. The hook-generated torque resists reorientation differently depending on flagellar location, facilitating surface escape for polar-flagellated bacteria while enhancing entrapment for lateral-flagellated bacteria. Our findings highlight the previously overlooked importance of flagellar placement in bacterial surface interactions, providing insights for understanding microbial ecology and designing biomimetic microswimmers.